Manual de planificación pedagógica para el perfeccionamiento del desempeño de los docentes de la unidad educativa ABC de la ciudad de Ambato. - Moreta Arce, Valeria Maritza (2018)
The present work is carried out with the purpose of strengthening the requirements of the current situation in the educational processes in the institution. The little application of the models issued by the Ministry of Education or the little knowledge of teachers without educational experience gives us the need to prepare a planning manual that is a guide in the organization of all the skills to be developed in each pedagogical unit. of the different educational levels. Pedagogical planning is an important part of the present and future life of educational institutions, highlighting pedagogical management as one of the fundamental pillars of student training, where the teacher and institution have in their hands the guidance and knowledge to impart to their students.